References In The Lyrics Of Nicole Zefanya’s Songs - Sravishta Ayundari Devi; I Made Rajeg; Putu Ayu Asty Senja Pratiwi (International Journal of Linguistics and Discourse Analytics, 2023)
In the current times, the use of cohesive devices is not only found in formal texts, but also in informal texts such as song lyrics. Accordingly, this study aims to identify the types and to analyze the functions of references from the lyrics of three songs by Nicole Zefanya; “Urs”, “Around”, and “Lose”. This study was conducted using descriptive quantitative method. Documentation method and note-taking technique were used to collect the data. In analyzing the data, this study used the theory from Halliday and Hassan (1976) about grammatical cohesion, to be specific, about reference. The analysis of data was presented using formal and informal method. The results of this study showed that all kinds of reference found in the lyrics of each song of Nicole Zefanya, namely personal reference, demonstrative reference, and comparative reference. Based on the analysis, the data in the lyrics are dominated by personal reference compared to demonstrative reference and comparative reference. In detail, personal reference with 169 occurrences, demonstrative reference with 42 occurrences, and comparative reference with 11 occurrences. Thus, each reference has different functions; as the head of reference, a reference to the previous object, as a modifier, a reference to the following object, a general comparison which refers to things that similar or not similar. Based on the results of this study, reference plays a vital role in establishing coherence, ensuring clarity, and contributing to the overall meaning of the song by connecting the language elements within the lyrics